HAYDAR XORAZMIYNING “GULSHAN UL – ASROR” MASNAVIYSIDA FORSCHA O‘ZLASHMA QATLAMGA OID LEKSEMALAR IFODASI - Ch.Tashmatova, N. (SCIENCE and SOCIETY, 2023)
In this article, the idioms expressed in the masnavi "Gulshan ul-asrar" by Heydar Khorazmi are classified and analyzed. In this research, we study the state of the lexemes of the self-identification layer presented in the Masnavi in a relatively new (after the Islamic and Mongol conquest) period. This group includes Arabic, Persian-Tajik and Mongolian adaptations.